Khảo sát cấu trúc đám hình thành khi gắn kết ure lên các bazơ nitơ trong chuỗi DNA bằng phương pháp hồi phục bán lượng tử - Thọ, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
The paper deals with studying on the ability of docking urea on nitrogen base groups of DNA by Semi-Quantum Relaxation method. The structural clusters were defined and the lengths of hydrogen bonds were calculated. The places in nitrogen base groups where urea molecule could form hydrogen bond being the same ones in double helix which are in a good very agreement with the references. It is proving that the algorithm was used is suitable and it will be extended to study different ligands. Introducing the studied method about the clusters were created by docking small molecules on the defined groups of macromolecules, which could not be studied successfully by cluster approximation on Gaussian or Gamess software.